An Analysis Rethorical Move and Step of Coffee Advertisement - Nurazizah Yova Ekaputri; Nakhwa Nabilla Atmaja; Lenni Herawati Sirait; Wina Avrillia Handyanto; Balqis Azwar Lubis; Thyrhaya Zein (Departement of Mathematics Education, 2025)
This study uses critical type analysis (CGA) to analyze a coffee brand's advertising brochure and focuses on its textual and visual strategies to attract consumers. The descriptive qualitative content analysis method was used. Using Bhatia's theory multilevel framework, the analysis spans four levels: text, genre, professional practice, and professional culture. On a textual level, concise language, eye-catching visuals, and clear calls to action can effectively inform and persuade your audience. Genre-level analysis highlights the dual purpose of these ads: to provide information and drive consumer engagement through targeted messaging. The results reveal the strategic use of rhetorical devices such as bold discounts (e.g., “50% off”), exclusive offers (“app only”), and promotional incentives (e.g., “Buy any 3, get 1 free”) that capture attention and create a sense of urgency. Visuals, such as tropical themes and vibrant product images, complement text elements to reinforce the brand image. Analysis of professional practices shows structured initiatives, including compelling headlines, product descriptions, and purchasing information, tailored to consumer preferences and market trends. At the professional and cultural levels, advertising reflects sociocultural norms and industry-specific marketing strategies, fostering trust and inclusion.